Perancangan Ulang Job Description untuk Mendukung Job Design yang Multitasking Berbasis Kompetensi Karyawan di PT. Pelindo III, Benoa, Bali - Billy Liang; Kriswanto Widiawan (Jurnal Titra, 2021)
PT. Pelindo III, Benoa, Bali is a company engaged in logistics services or can be referred to as a dock or port managed by Indonesian SOEs. The problem that occurs is that workers or employees do multitasking in carrying out job descriptions. This research was conducted so that the multitasking job description can be carried out properly and optimally. Researchers identify and analyze job descriptions and job competencies, so that job descriptions designed based on employee competence in accordance with the abilities and skills of each employee. There are some job descriptions that are designed that are not appropriate, such as job descriptions for managers, because some of the job descriptions that are carried out should be carried out by the security division. The job description will be readjusted once the Security Division has been established. The redesigned job description can be said to be quite good and can be accepted by every employee who performs a multitasking job description.